ADVANTAGES OF NEW TECHNOLOGIES IN EDUCATION (Scientific journal of the Fergana State University, 2023)
The article examines the modern understanding of innovative technologies, their role and significance. The tasks of the advantages of new technologies in education, the use of various teaching methods in problem-based learning, problem solving, solutions to situations and prospects in this innovative technologies are considered. The effect of informatization and digitalization of the educational process is considered, which should create a firm confidence that these qualities of the organization of the educational process are characteristic of the entire modern society, the design of training in accordance with the requirements of the time, the use and development of logical thinking operations.